First epidemiological survey of Toxoplasma gondii in Galapagos sea lions (Zalophus wollebaeki) - Mosquera Juan D.; Diaz Eduardo; de los Ángeles Bayas Rosa; Páez-Rosas Diego; Grijalva-Rosero Colón Jaime; Zapata Sonia; Escotte-Binet Sandie; Di Brasi Quentin; Villena Isabelle; Poulle Marie-Lazarine (Parasite)
Toxoplasma gondii is the protozoan parasite responsible for toxoplasmosis, a zoonosis that represents a health risk for mammals, including marine species. Felines are the only definitive hosts of this parasite, playing a critical role in the introduction and maintenance of the pathogen in a new environment. Recent data demonstrate the contamination by T. gondii of the terrestrial and seawater environment of the Galapagos archipelago, in the Pacific Ocean. Little is known about the exposure of Galapagos’ threatened species to T. gondii, although introduced domestic cats in the archipelago are known to be seropositive for T. gondii. We documented for the first time exposure to T. gondii of Galapagos sea lions (Zalophus wollebaeki), an endemic and emblematic species of the archipelago. The modified agglutination test revealed the presence of antibodies against T. gondii in 61 of 77 plasma samples collected in 2016–2017 from 2- to 4-year-old wild sea lions live-handled in their breeding sites on the inhabited island of San Cristóbal. Antibodies were also detected in 4 of 19 serum samples (21%) from sea lions whose corpses were found in 2021 on the same island. In addition, T. gondii DNA was detected in a lung sample from one necropsied pup and a tissue cyst-like structure was found in another, suggesting infection. These results, together with the high prevalence of antibodies in 2 to 4-year-olds, indicate that Galapagos sea lions are frequently exposed to T. gondii and raise concerns that toxoplasmosis may pose a threat to this endemic species.